2015
DOI: 10.1123/jpah.2014-0307
|View full text |Cite
|
Sign up to set email alerts
|

Objective Analysis of Preschoolers’ Physical Activity Patterns During Free Playtime

Abstract: Preschool children gradually became more active during the first 10 to 15 minutes of outdoor gross motor playtime and less active over the final 10 to 15 minutes of playtime. During the second half of playtime 3-year-olds maintained these changes to a greater degree than 4- and 5-year-olds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Three periods of outdoor free-play was selected as: i) research has demonstrated repeated spikes in activity across the day in childcare coinciding with scheduled breaks [13, 16]; and ii) that the start of such breaks stimulate between 3 and 15 min of intense activity, sufficient to achieve an additional 10 min MVPA [27]. The minimum period of outdoor free-play of 15 min was selected given evidence that MVPA often attenuates after this period [13].…”
Section: Methodsmentioning
confidence: 99%
“…Three periods of outdoor free-play was selected as: i) research has demonstrated repeated spikes in activity across the day in childcare coinciding with scheduled breaks [13, 16]; and ii) that the start of such breaks stimulate between 3 and 15 min of intense activity, sufficient to achieve an additional 10 min MVPA [27]. The minimum period of outdoor free-play of 15 min was selected given evidence that MVPA often attenuates after this period [13].…”
Section: Methodsmentioning
confidence: 99%
“…To achieve this, we propose targeting setting-specific characteristics that have been shown to positively affect higher-intensity PA. Such characteristics include (1) childcare providers (i.e., PA-specific training; personal attitudes toward PA; and presence of supportive behaviors, such as prompts and role modeling), 10 , 11 , 12 (2) physical environment (i.e., portability of equipment, quality, and amount of space available for energetic play), 10 , 13 , 14 (3) outdoor time (unstructured play and shorter, more frequent bouts), 4 , 15 and (4) policies specific to the promotion of PA (e.g., optimal dose and intensity during hours of care) at all levels of governance and administration. 16 Considering these findings, deliberate, evidence-informed action can be undertaken to support increased opportunities for energetic play in childcare environments.…”
Section: A Call To Actionmentioning
confidence: 99%
“…The type of outdoor play (e.g., unstructured vs. structured/adult-led) has also been examined as a mechanism to support improved PA in childcare. 4 The provision of outdoor, unstructured free play has been linked to increasing young children's levels of energetic play 4 , 15 and as such should be encouraged by childcare staff and supported by center-enforced policies. A shift in focus from indoors (highly sedentary pursuits) to outdoors (more energetic free play) during childcare could result in improvements in physical health, 9 learning outcomes, and psychosocial function.…”
Section: Childcare-specific Mechanisms For Increasing Energetic Playmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a body of evidence suggesting that long duration (≥30 minutes per session) PA interventions may not be effective for young children because young children tend to accumulate the majority of their high-intensity PA within the first 10 minutes of playtime. [6][7][8] For example, McKenzie et al demonstrated that, within a 30-minute recess period, elementary and preschool school-age children tend to accumulate the majority of their MVPA during the first 10 minutes of play, with the remaining 20-minute block spent in sedentary to light intensity activities. 6 The longer children participate in a given game or activity, the less activity they accumulate during the entire period of the activity.…”
mentioning
confidence: 99%